Repositioning of Hypoglycemic Drug Linagliptin for Cancer Treatment - Li, Yong; Li, Yiqun; Li, Dengke; Li, Kaiming; Quan, Zhengyang; Wang, Ziyi; Sun, Zhenxiao (Frontiers in Pharmacology, 2020)
Drug repositioning, development of new uses for marketed drugs, is an effective way to find new antitumor compounds. In this study, we used a new method to find key targets combination, which was used to filter compounds by molecular docking. The data of gene expression of colorectal cancer, breast cancer, liver cancer tissue and normal tissues were obtained from TCGA. The key targets combination was obtained from the protein-protein interaction network (PPI network) and the correlation of targets analysis. Molecular docking was used to reposition the drugs which were obtained from DrugBank. MTT proliferation assay and animal experiments were used to verify the activity of candidate compounds. Flow cytometric analysis of proliferation, cell cycle and apoptosis, slice analysis, gene regulatory network and Western blot were used to further explain the mechanism of action of drugs. CDK1 and AURKB were chosen as the combination of key targets by the analysis of different expression gene from TCGA. We computationally predicted twelve compounds against tumors and the three compounds, linagliptin, mupirocin, and tobramycin, were verified inhibiting cell viability in human colorectal HCT116, breast cancer MCF-7 and liver cancer HepG2 cells in vitro. Linagliptin, a hypoglycemic drug, was proved to inhibit cell proliferation by cell cycle arrest and inducing apoptosis in HCT116 cells, and suppress tumor growth in nude mice bearing HCT116 cells. Linagliptin reduced the tumor size and decreased the expression of Ki67, a nuclear protein which is expressed in all proliferative cells. Gene regulatory network and Western blot analysis suggested that linagliptin inhibit tumor cell proliferation and promote cell apoptosis through suppressing the expression and phosphorylation of Rb, down-regulating expression of Pro-caspase3 and Bcl2, respectively. The combination of key targets based on the protein-protein interaction network which were built by the different gene expression of TCGA data to reposition the markted drugs was turned out to be a new approach to find new antitumor drugs, the hypoglycemic drug linagliptin could potentially lead to novel therapeutics for the treatment of tumor, especially in colorectal cancer, and gene regulatory network is a worthwhile approach to predict and explain the mechanism of action of drugs.